Proposed guidelines for libraries for the blind in the Philippines based on the British Council of Museums, Archives, and Libraries' Best Practice Manual for Library Service for Visually Impaired People and evaluation of the Philippine National School for the Blind - Paraan, Ronald Gonin C.; Timoteo, Christine B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
Libraries have always been an important institution in society as an accessible source and repository of knowledge. Accessing and using libraries are fairly simple for the regular library users but the situation is different for people who have visual impairments. Visually Impaired People are generally unable to use the regular materials found in a common library and the best solution to this drawback is to provide the proper library services that fit the need of the visually impaired.
Guidelines are used as tools for institutions to provide quality service to their clients. At present, there are no readily available guidelines for libraries for the blind in the Philippines and it is because of this that the study aimed to formulate one based on Resource's Best Practice Manual for providing library service to the visually impaired together with the evaluation of the Philippine National School for the Blind (PNSB). Based on the best Practice Manual, the key areas for providing quality library service to the visually impaired are: (a) Legal Bases and Awareness; (b) Management and Service Policies; (c) Available Library Services; (d) Alternative Formats, Collection Development, Assistive Technology and Availability; (e) and Accessibility and Design. Out of the 40-high school students of the PNSB, 29 were interviewed along with the school's Guidance Councilor/Social Worker and computer subject teacher. Additional information was also received from an interview with the Resources for the Blind, Inc.
The data and information gathered in the course of the study implied that: (a) locally, R.A. 7277 or the Magna Carta for Disabled Persons contains information that may be used for the improvement of providing library service for the visually impaired; (b) The Architectural and Accessibility for the Disabled manual of the Philippine Foundation for the Rehabilitation of the Disabled, Inc. provides valuable information on interior/exterior design which provides better accessibility for the disabled including the visually impaired; (c) the PNSB library is able to provide its users basic needs but may significantly improve its performance and service by hiring a fulltime librarian; (d) the PNSB library's collection is mostly made up of braille materials, followed by the large print, and one CCTV; (e) the majority of the PNSB library users only use the library when required and commonly use it for homework, assignments, and research; (f) in the Philippines, the most common and available alternative format materials are braille and large print, there are also audio and recording materials but are said to be difficult to maintain; (g) electronic media and assistive technology for the visually impaired like CCTV's talking personal computers, electronic embossers, and enlarging photocopiers are available in the Philippines, most of which may cost a lot but their acquisition may prove to be a wise investment.
The general recommendation was that present and future libraries for the blind review the proposed set of guidelines of the study to gain information on possible steps to take for the improvement of providing library services to the visually impaired. Other recommendations included were: (a) the hiring of a full-time librarian for the PNSB library; (b) libraries for the blind should constantly review their user and potential user needs and find ways to generate extra funds; (c) libraries for the blind should also acquire regular print materials for proper transcription to alternative formats; (d) that library staff of libraries for the blind should be aware of the media and technology available; (e) institutions should be aware of equal treatment and accessibility for the disabled.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and the blind -- Philippines; Philippine National School for the Blind